Gametogenesis, seasonal reproduction and imposex of Adelomelon beckii (Neogastropoda: Volutidae) in Mar del Plata, Argentina - Arrighetti, F. (2010)
Adelomelon beckii (Broderip, 1836) (Neogastropoda: Volutidae) is endemic to the western south Atlantic coast. It inhabits sandy bottoms in waters between 40 and 70 m deep and is one of the largest top benthic predators found in Mar del Plata, Argentina. The present study describes gametogenesis and the reproductive cycle of this species. Oocytes developed in close association with follicle cells, which appear to play a role in yolk synthesis and oocyte resorption, providing the key functions of phagocytosis and intracellular digestion of degenerating oocytes. Spermatogenesis resembles that reported for other volutids. The reproductive cycle of A. beckii in Mar del Plata was studied over a period of 2 yr (September 2004 to August 2006). Gametic emission in males continued throughout the year while females showed 2 spawning periods: one during spring (September-November) and another during autumn (March-April). In females, this semi-annual pattern appears to be related to the seasonal variation in seawater temperature, coinciding with observations made in other volutes. In males, there was no relationship to variation in seawater temperature, an unusual pattern for a species from a temperate region. Imposex was described for the first time in this species. These data constitute baseline information for establishing appropriate and biologically based management and conservation strategies for this overexploited gastropod species. © Inter-Research 2010.